The prevalence of careless response behaviour and its consequences on data quality in self-report questionnaires on student learning - Chauliac, Margot; Willems, Jonas; Gijbels, David; Donche, Vincent (Frontiers in Education, 2023)
Introduction Self-report questionnaires are widely used in high schools and universities to gain insights into students’ learning strategies and enhance the quality of their education. However, it is important to acknowledge the possibility of respondents being inattentive when completing these questionnaires. While reliability analyses are typically performed at the group level, when providing individual feedback, it is crucial that each respondent’s results are reliable. This study aimed to evaluate the prevalence of careless response behaviour in a questionnaire concerning student learning. Methods Data analysis encompassed a substantial sample of 12,000+ students in their final two years of secondary education, averaging around 17 years of age. Employing five complementary detection techniques, the study identified instances of careless responding present in the questionnaire data. Results Our results underscore a notable prevalence of careless response behaviour among the surveyed students. Application of the five detection techniques revealed a substantial number of instances indicating inattentive responding. Furthermore, the questionnaire’s measurement scales were evaluated for reliability. The study noted the presence of carelessness but observed minimal impact on group-level results. Discussion The outcomes of this study hold important implications for using self-report questionnaires in education. The prevalence of careless responding emphasizes the need for scrutinizing individual responses. Despite careless responses, their influence on overall group-level data integrity seems restricted. Nonetheless, the study underscores the importance of cautiously interpreting individual-level outcomes, particularly when using these results for individual feedback.